2009
DOI: 10.1093/molehr/gap013
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of progesterone receptor A isoform in mice leads to endometrial hyperproliferation, hyperplasia and atypia

Abstract: A delicate balance in estrogen and progesterone signaling through their cognate receptors is characteristic for the physiologic state of the endometrium, and a shift in receptor isotype expression can be frequently found in human endometrial pathology. In this study, using a transgenic mouse model, we examined the mechanisms whereby alterations in progesterone receptor (PR) isotype expression leads to endometrial pathology. For an experimental model, we used transgenic mice (PR-A transgenics) carrying an imbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
(44 reference statements)
0
12
0
1
Order By: Relevance
“…This delicate balance of PR isoforms is further illustrated with transgenic mice overexpressing PR-A in glandular epithelium and stromal tissue. This experimental increase in the PR-A:PR-B ratio results in endometrial hyperplasia and atypia with enhanced expression of uterine epithelial growth factors such as amphiregulin known to be regulated by progesterone; these effects can be abolished by treatment with the anti-progestin, mifepristone (Fleisch, et al 2009). These results show that progesterone can be either an anti- or pro-proliferative force on the endometrium depending on isoform expression.…”
Section: Uterusmentioning
confidence: 99%
“…This delicate balance of PR isoforms is further illustrated with transgenic mice overexpressing PR-A in glandular epithelium and stromal tissue. This experimental increase in the PR-A:PR-B ratio results in endometrial hyperplasia and atypia with enhanced expression of uterine epithelial growth factors such as amphiregulin known to be regulated by progesterone; these effects can be abolished by treatment with the anti-progestin, mifepristone (Fleisch, et al 2009). These results show that progesterone can be either an anti- or pro-proliferative force on the endometrium depending on isoform expression.…”
Section: Uterusmentioning
confidence: 99%
“…Fertil Steril 2011. related to reduced expression of progesterone-dependent genes, especially in the secretory phase of the menstrual cycle (55). The physiologic effects of progesterone in the uterus are varied (33), but some recent studies have suggested that the development of uterine abnormalities, such as adenomyosis and cancer, might arise from a ''misregulation in the relative expression of the two main PR isoforms'' rather than PR expression being a marker of disease (56). Our data in the human suggest this might be the case because PR-A/ PR-B ratios remained similar to those of the normal uterus, albeit with consistently lower PR-A and PR-B expression in adenomyosis.…”
Section: Figurementioning
confidence: 99%
“…P4 activates two subnuclear receptors or transcription factors, raising the possibility that each of these two P4 actions may be mediated by a different P4 receptor. This hypothesis is supported by several studies performed in a variety of normal and dysplastic cells showing that P4 receptor A (PR-A) and PR-B have different functions (8,16,23,32). We have shown that PR-B is responsible for downregulating Gq/11 because P4 receptor transfection of normal colon muscle cells increases their sensitivity to P4-reduced Gq/11 protein expression and impaired contraction (8).…”
mentioning
confidence: 61%
“…P4, VIP, 8=bromo-c=AMP (8B-c=AMP), (16), and G protein subunit antibodies were purchased from CytoSignal (Irvine, CA), and antibodies against PR-A and PR-B were from Cayman Chemical (Ann Arbor, MI) (13).…”
Section: Methodsmentioning
confidence: 99%